Designing devices for global surgery: evaluation of participatory and frugal design methods. Issue 1 (11th January 2021) - Marriott Webb, Millie; Bridges, Philippa; Aruparayil, Noel; Mishra, Anurag; Bains, Lovenish; Hall, Richard; Gnanaraj, Jesudian; Culmer, Peter
Abstract : Introduction: Most people living in low- and middle-income countries have no access to surgical care. Equipping under-resourced health care contexts with appropriate surgical equipment is thus critical. "Global" technologies must be designed specifically for these contexts. But while models, approaches and methods have been developed for the design of equipment for global surgery, few studies describe their implementation or evaluate their adequacy for this purpose. Methods: A multidisciplinary team applied participatory and frugal design methods to design a surgical device for gasless laparoscopy. The team employed a formal roadmap, devised to guide the development of global surgical equipment, to structure the design process into phases. Phases 0–1 comprised primary research with surgeons working in low-resource settings and forming collaborative partnerships with key stakeholders. These participated in phases 2–3 through design workshops and video events. To conclude, surgical stakeholders (n=13) evaluated a high-fidelity prototype in a cadaveric study. Results: The resulting design, "RAIS" ( R etractor for A bdominal I nsufflation-less S urgery), received positive feedback from rural surgeons keen to embrace and champion innovation as a result of the close collaboration and participatory design methods employed. The roadmap provided a valuable means to structure the design process but this evaluation highlighted the need for further development to detail specific methodology. The project outcomes were used to develop recommendations for innovators designing global surgical equipment. To inform early phases in the design roadmap, engaging a variety of stakeholders to provide regular input is crucial. Effective communication is vital to elucidate clear functional design requirements and hence reveal opportunities for frugal innovation. Finally, responsible innovation must be embedded within the process of designing devices for global surgery. Conclusion: A community-wide effort is required to formally evaluate and optimize processes for designing global surgical devices and hence accelerate adoption of frugal surgical technologies in low-resource settings.